Samoa : Financial Sector Assessment Program-Banking Supervision and Regulation-Technical Note. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note discusses the key findings and recommendations of assessment of Banking Supervision and Regulation for Samoa. Little progress has been achieved toward implementing the recommendations of the 2007 Basel Core Principles for Effective Banking Supervision assessment. Initiatives by the Central Bank of Samoa to deal with weaknesses identified in supervision and regulation of domestic banks in 2007 were disrupted by a series of natural disasters and the use of limited supervisory resources on other priorities. Progress was achieved, however, in issues related to Anti-Money Laundering and Combating Financing of Terrorism, with Samoa upgraded to a 'normal reporting" regime by the Asia Pacific Group on Money Laundering in 2014, from its previous status of "enhanced reporting.".